Spatial optimization of agricultural production from the perspective of “Greater Food Concept” in Yangzhou, China - Xin Li; Xin Xu; Ru Meng Yin (Ecological Indicators)
Global food security continues to face serious challenges. The “Greater Food” perspective can guarantee regional food security and the availability of basic agricultural products. However, there is still a lack of an appropriate methodology to optimize the spatial agricultural production system under the concept of “greater food.” In this study, we quantitatively analyzed agricultural production space’s quality and spatial distribution characteristics using multi-scale fusion and ecological niche suitability models. The results showed that The overall level of agricultural production function in Yangzhou was high, with firm spatial heterogeneity, high in the southeast and low in the southwest bounded by the line of Gaoyou Lake. The distribution pattern was closely related to the land use status, urban development, topography, and spatial functional positioning of the national territory. The natural quality of agricultural production was better, and the spatial form was more regular and compact. However, due to the coercion of urbanization and industrialization development, the overall ecological location suitability was average. The suitability around the built-up areas, Gaoyou Lake, Baoying Lake, and the Yangtze River was generally low. Based on the results of the comprehensive evaluation of agricultural production functions and ecological suitability, it could be divided into four areas: core protection area, integration and optimization area, comprehensive improvement area, and restricted development area. We plan to propose a classification and optimization strategy accordingly. The method of this study synthesized the multifunctionality and suitability of land use for agricultural production space identification. In this way, it may provide innovative ideas for delineating agricultural production space in economically developed areas, which could guide the optimization of agricultural production space with high quality.